Rising NPAs and Start Up India Initiative : A Possible Venture - Singh, Dr. Alka (International Journal of Scientific Research and Management (IJSRM), 2017)
The Indian banking sector has been facing serious problems of raising Non-Performing Assets (NPAs). The NPAs has a direct bearing on the growth and profitability of banks. The NPAs are one of the major concerns for scheduled commercial banks in India. Based on the recommendations of Narasimham committee and Verma committee, some steps have been taken to manage the NPA problem in the balance sheets of the banks. As such there was no unanimity in terms of the policies followed by various banking istitutions in resolving this problem. The figure of NPAs reflect the performance of banks. The banks unable to manage its high level of NPAs is reflective of large number of credit defaults that affect the profitability and net-worth of banks and also erodes the value of the asset. The NPAs not only affect the liquidity and profitability but also pose threat on quality of asset and survival of banks. The NPAs not only affects the profitibity of the banks but also affects the economy of the country. High level of NPAs as reflective in Indian banks is also a reflection of the state of health of the industry and trade. It is very much pertinant to reduce the NPAs in order to improve the financial health in the banking system. There may be various reasons for generation of these NPAs which may be due to improper assesment or fraud. This paper proposes a solution which in turn is also an start up India initiative to minimise the reasons for creation of these NPAs.